Relationship between cardiac cycle and the timing of actions during action execution and observation - Palser, Eleanor R; Glass, James; Fotopoulou, Aikaterini; Kilner, James M (bioRxiv, 2020)
Previous research suggests that there may be a relationship between the timing of motor events and phases of the cardiac cycle. However, this relationship has thus far only been researched using simple isolated movements such as key-presses in reaction-time tasks and only in a single subject acting alone. Other research has shown both movement and cardiac coordination among interacting individuals. Here, we investigated how the cardiac cycle relates to ongoing self-paced movements in both action execution and observation using a novel dyadic paradigm. We recorded electrocardiography (ECG) in 26 healthy adult subjects who formed 19 dyads (7 comprised of two subjects and 12 subjects paired with an experimenter). Each dyad contained an action executioner and observer as they performed a self-paced sequence of movements. We demonstrated that heartbeats are timed to movements during both action execution and observation. Specifically, movements were less likely to culminate synchronously with the heartbeat, around the time of the R-peak of the ECG. The same pattern was observed for action observation, with the observer's heartbeats occurring off-phase with movement culmination. These findings demonstrate that there is coordination between an action executioner's cardiac cycle and the timing of their movements, and that the same relationship is mirrored in an observer. This suggests that previous findings of interpersonal coordination may be caused by the mirroring of a phasic relationship between movement and the heart. Competing Interest Statement The authors have declared no competing interest.